Analysis of Hydrodynamic Performance in Flexitank Applications with Varying Strap Configurations Using CFD - MUHAMMAD HISYAM BIN MOHD AZARAN; NOFRIZALIDRIS BIN DARLIS; IZUAN AMIN BIN ISHAK (Progress in Engineering Application and Technology, 2025)
Liquid sloshing is a fundamental challenge in the structural design of flexitank used for liquid transportation. Thus, flexitank is one of the alternative ways for transporting the fluid package. However, there are some cases reported by industry regarding the leakage of the flexitank during transportation. The purpose of this study is to analysis of hydrodynamic performance in flexitank application with varying straps configurations using CFD software which is Ansys Software. For the geometry of flexitak, Blender Software are used because it make the model more 3D. In this study, the straps act like a baffle in the ISO tank. There are several types of straps configurations in this study which are the number of straps and depths of straps likes one strap, two straps and three straps for the number of straps, while the depts of straps are 1/3, 1/2 and 2/3 of height the flexitank. By simulating these configurations, the research aims to identify optimal designs that minimize sloshing, improve pressure management, and reduce wall shear stress. The study provides a comprehensive understanding of how strap placement influences hydrodynamic forces, contributing to the development of safer and more efficient flexitank systems for liquid transportation.